The Historical Soundscape Analysis of Fatahillah Square, Jakarta - Michael Isnaeni Djimantoro; Widjaja Martokusumo; Heru W. Poerbo; R. Joko Sarwono (Acoustics, 2020)
Understanding conceptions of the protection of cultural heritage continues to develop until now. Presently, urban historic places are not only comprehended as tangible but also include intangible dimensions. However, the conservation of cultural heritage dominantly still emphasises the visual sense more than any other senses. Thus, this paper addressed several questions on the role of human senses, the historic sonic environments, and the soundmarks of the past in examining a historical area. This paper aims to reveal the relation between sound sources and its predicted sonic environment in historic places over the time. The case study was Fatahillah Square, Jakarta, which has been documented from the 19th century until now. Some methods were carried out such as soundwalk, recalled in memory, and visual analysis. The results show that comprehensive study of multisensorial stimulus can increase a holistic understanding of historic places. Therefore, the protection of historic sites cannot only focus on the object per se, but also it must be considered to be a holistic entity. This research highlights new perspectives in analysing historical areas using combination of pictorial sources and sonic information.